1998
DOI: 10.1002/(sici)1097-4601(1998)30:5<335::aid-kin3>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and mechanism of chromic acid oxidation of oxalic acid in absence and presence of different acid media. A kinetic study

Abstract: Kinetics and mechanism of the reaction of Cr (VI) where only undissociated oxalic acid is kinetically active. Kinetic evidence for the formation of a Cr(VI)9 oxalic acid 1 : 1 complex has been obtained and the equilibrium constant for their formation has been determined. The 1 : 1 complex exists most likely in an open chain form. The rate-limiting step of the oxidation reaction involves the breaking of the C9 C bond in the 1 : 2 complex. Oxidizing ability of Cr(VI) species have been discussed. Mechanism with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Fast Ϫ иCO ϩ Cr(VI) 9 9 : Cr(V) ϩ CO 2 2 Fast Cr(V) ϩ (COOH) 9 9 : 2CO ϩ Cr(III) 2 2 Earlier studies lend strong support for this scheme [20]. The activation enthalpies and entropies of the oxidation of benzanilides by Cr(VI) in the presence of oxalic acid in aqueous acetic acid medium are linearly related (Table III).…”
Section: Scheme IIImentioning
confidence: 75%
“…Fast Ϫ иCO ϩ Cr(VI) 9 9 : Cr(V) ϩ CO 2 2 Fast Cr(V) ϩ (COOH) 9 9 : 2CO ϩ Cr(III) 2 2 Earlier studies lend strong support for this scheme [20]. The activation enthalpies and entropies of the oxidation of benzanilides by Cr(VI) in the presence of oxalic acid in aqueous acetic acid medium are linearly related (Table III).…”
Section: Scheme IIImentioning
confidence: 75%
“…Previous studies have shown OX to have a significant role in both Cr(VI) reduction and Cr(III) complexation [14,44,45]. CA also can increase the reduction of Cr(VI) and the subsequent formation of soluble Cr(III)-citrate [45], and solubilize the Cr(III) by complexation and desorb the Cr(VI) by competition for surface sites [24].…”
Section: Resultsmentioning
confidence: 99%